Effect of Slot Jet Flow on Non-Axisymmetric Endwall Cooling Performance of High-Load Turbines - Kun Du; Yihao Jia; Hui Song; Lei Chen; Qian Zhang; Tingting Cui; Cunliang Liu (Machines, 2023)
As vane inlet temperatures and turbine loadings are increasing, the aerodynamic and thermal management for the endwalls of gas turbines have received increased attention. Non-axisymmetric endwalls are becoming popular due to their proficient capabilities to modify the secondary flow fields and to change the film cooling performance on the endwalls. In this study, by considering the interaction between mainstream and purge flow based on non-axisymmetric endwall contouring, the numerical research model used in the present research was established. Based on the validated numerical method, the influence of the non-axisymmetric endwall contouring on the film-cooling effectiveness and aerodynamic characteristics was studied. Furthermore, the effect of different inclination angles on the film-cooling performance of the contoured endwalls was also investigated. The results indicate that for the high-load turbine vane used in this research, various types of non-axisymmetric endwall contouring can alter the aero-dynamic characteristics and cooling performance simultaneously. By inhibiting the secondary flows, non-axisymmetric endwall contouring can reduce the total cascade pressure loss coefficient by 0.305%. In addition, non-axisymmetric endwall contouring can significantly enhance the effective coverage area of purge flow up to 28.29%, and the endwall near the suction side can achieve better cooling performance. Finally, non-axisymmetric endwall contouring can improve the protective effect of large-angle purge flow.